The power stage design of class - D amplifier - Su, Li Wei (2015)
Class-D amplifier is a switching amplifier and mostly is also called a Pulse Width Modulation (PWM) amplifier. It can operate with the switches either fully off or fully on so that its efficiency can be very high. With the development of Class-D amplifier, now it is widely used in many systems such as speakers, motors, audio and various transducers. This report has designed a power stage of Class-D amplifier with full-bridge configuration. Because the Class-D amplifier is still at study phase, there are so many opportunities to improve and apply. The design in this report is able to amplifier the audio signal and has a small Total Harmonic Distortion (THD) level. It can be applied to some audio systems. Moreover, after reading many literatures, in this report, it introduces the basic principles of Class-D amplifier such as PWM, AD and BD modulations and THD. It also makes some comparisons. For instance, comparing Class-D with Class-A amplifier, Class-B amplifier and Class-AB amplifiers. Full-bridge Class-D is compared with full-bridge Class-D. Virtuoso Platform that is provided by Cadence conducts all the circuit designs and simulations. The process of Global Foundries 0.18 μm CMOS is selected in the design.